Central limit theorem for stochastically additive functionals of ergodic chains - Moskal'tsova, N. V.; Shurenkov, V. M. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
A central limit theorem is proved for stochastically additive functional of ergodic Markov chains.